Pelatihan Pengembangan Konten, Proses, dan Produk Pembelajaran Berdiferensiasi untuk Guru MGMP Bahasa Inggris SMP/MTs Kota Padang Panjang - Zainil, Yetti; Adnan, Aryuliva; Yusra, Siti Rahimah; Ayudhia, Honesty Yonanda; Hanifa, Rizaldy (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2024)
The implementation of Kurikulum Merdeka supports student-centered and flexible learning methods as reflected in Differentiated Learning (DL). Through this learning method, teachers would prepare learning materials, delivery, as well as evaluations by referring to students’ readiness, willingness, and preferences in learning. Therefore, teachers’ roles are essential in identifying and supporting the students’ needs to make sure that the learning processeswould run smoothly to reach maximum results. So far, the implementation of DL is delayed due to teachers’ unreadiness to apply the new curriculum and their preference to continue teaching based on the previous curriculum. For that reason, the current curriculum could not be implemented well. Due to this matter, a training to encourage teachers’ competences in preparing English lessons based on DL is proposed. In this activity, Junior High School/Madrasa English teachers in Padang Panjang were gathered in a training of Differentiated Learning to improve the teachers’ understanding about DL and help with the necessary preparation to implement the DL-based lessons in their classrooms. During the training, teachers were asked to participate in workshops, discussions, and being involved in a special project where participants were asked to create lesson plans in line with concepts of differentiated learning.